(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To systematically synthesize available evidence on the incidence of postoperative cognitive dysfunction (POCD) in older adults undergoing surgery under regional anesthesia. Research and methods: A systematic review was conducted in accordance with the PRISMA. Relevant studies were identified through searches of PubMed/MEDLINE, HINARI, and Google Scholar. Eligible studies included patients aged 60 years or older who underwent surgery under spinal, epidural, regional, or neuraxial anesthesia. Results: Ten studies met the inclusion criteria and were included in the analysis. The reported incidence of POCD after regional or spinal anesthesia ranged from 4.25% to 36.6%. Pooled analysis using a random-effects model showed an overall incidence of POCD within 7 days after surgery of 15% (95% confidence interval: 9%–24%), with substantial heterogeneity among studies. Conclusion: Postoperative cognitive dysfunction remains a relatively common complication in elderly patients undergoing regional or spinal anesthesia, with an estimated incidence of approximately 15% in the early postoperative period.